P12.03 A Delphi survey to inform core 'red flag' symptoms for an electronic patient reported outcome system in glioblastoma follow up. (9th September 2021) - Luis, A; Boele, F; Booth, T
Abstract: BACKGROUND: Glioblastoma is a common and aggressive primary malignant brain tumour in adults associated with a poor prognosis and considerable symptom burden. Clinical review and serial neuroimaging remain the primary monitoring tools to assess for disease status. However, the evidence base for the existing surveillance imaging schedule is yet to be established. New models of follow up care are needed to demonstrate better patient outcomes in this patient cohort. There are indications that patient-reported outcome measures (PROMs) can contribute to improved survival and maintaining an optimal quality of life in other oncology populations. MATERIALS AND METHODS: There are no standardised PROMs for the priority symptoms in glioblastoma patients, which can be used for evaluation in clinical care as a surrogate marker for disease progression. A broad set of symptoms were therefore initially identified in a targeted literature search and were further refined via Delphi methodology, with the aim to obtain consensus amongst a small expert panel involved in the care of glioblastoma patients. A three round Delphi email survey was conducted. Consensus was defined as 70% agreement. RESULTS: Symptom and function constructs were assessed for relevance, relationship to disease and treatment, sensitivity to change, psychometric properties and patient acceptability. Consensus was reached on the red flag symptoms and symptom clusters to monitor, as well as the minimum severity thresholds needed to trigger an alert on an electronic symptom reporting system, which has been developed to allow patient self-reporting of symptoms during treatment. CONCLUSION: The red flag symptoms to monitor, along with the symptom severity thresholds, informed an app-based symptom reporting system, which is currently being piloted in a feasibility study exploring triggered imaging using ePROMs. This has the potential to inform future clinical practice through development of patient reported biomarkers.